The University Perspective: A Summary of Two Panel Sessions at the AFB Leadership Conference Concerning Educational Topics. (March 2019) - McManus, Hailey; McManus, Chantal
Editor's Note : This commentary is based on the conference sessions, "Preparing Teachers to Work with Students with CVI: The University Perspective, " by Laura Bozeman, Mindy Ely, Kathryn Botsford, and Yue-Ting Siu; and "Mentoring Doctoral and Other Students to Contribute Critical Research to JVIB, " facilitated by Sandra Lewis, Rona Pogrund, and Rebecca Burrichter, which took place Thursday, February 28, 2019, and Friday, March 1, 2019, respectively, at the American Foundation for the Blind (AFB) Leadership Conference in Arlington, VA.